Reflection and Reflexivity in Practice Versus in Theory: Challenges of Conceptualization, Complexity, and Competence - Alexander, Patricia A. (Educational psychologist, 2017)
In this commentary, theoretical principles pertaining to the role of epistemic cognition in teaching and professional development, synthesized from the content of this special issue on reflection and reflexivity, are proffered. These theoretical notions are then followed with a critical analysis of specific challenges encountered in enacting these principles in practice. Those challenges include the conceptual demands placed on educators who must interpret the expanding lexicon of epistemic cognition, especially when that lexicon is vaguely defined. There is also the complexity that exists within everyday educational settings where nonepistemic concerns must also be addressed and where external and internal forces continually shape the flow of instruction. Finally, there is the challenge of fostering epistemic competence in teachers and students, where attention to contextual factors such as the subject matter, specific task, and significance of the problem become part of the epistemic calculus, influencing epistemic aims, goals, and outcomes.